NEW ORCHID RECORDS FROM ATLANTIC CENTRAL AFRICA - Droissart, V.; Sonké, B.; Simo, M.; Stévart, T. (Edinburgh Journal of Botany, 2009)
Several papers dealing with Orchidaceae from Atlantic Central Africa have recently been published. However, orchid distributions in this area remain poorly known. Over the last decade, we have conducted an intensive fieldwork programme in Cameroon and Equatorial Guinea. This has enabled us to collect 22 taxa that are new national records. Ten taxa are new records for Cameroon, eight for Equatorial Guinea and four for both countries. One of these taxa is also a new record from Nigeria. Fifteen taxa are endemic to the Lower Guinea area and six were previously known only from the type locality.
Keywords: Atlantic Central Africa; Cameroon; Equatorial Guinea; new national records; Nigeria; Orchidaceae